Saponins of ginseng products: a review of their transformation in processing - Ye, Xian-Wen; Li, Chun-Shuai; Zhang, Hai-Xia; Li, Qian; Cheng, Shui-Qing; Wen, Jia; Wang, Xuan; Ren, Hong-Min; Xia, Liang-Jing; Wang, Xu-Xing; Xu, Xin-Fang; Li, Xiang-Ri (Frontiers in Pharmacology, 2023)
The primary processed product of Panax ginseng C.A. Meyer (P. ginseng) is red ginseng. As technology advances, new products of red ginseng have arisen. Red ginseng products, e.g., traditional red ginseng, sun ginseng, black ginseng, fermented red ginseng, and puffed red ginseng, are commonly used in herbal medicine. Ginsenosides are the major secondary metabolites of P. ginseng. The constituents of P. ginseng are significantly changed during processing, and several pharmacological activities of red ginseng products are dramatically increased compared to white ginseng. In this paper, we aimed to review the ginsenosides and pharmacological activities of various red ginseng products, the transformation law of ginsenosides in processing, and some clinical trials of red ginseng products. This article will help to highlight the diverse pharmacological properties of red ginseng products and aid in the future development of red ginseng industrialization.